2000
DOI: 10.1103/physrevb.61.8270
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for strain in and around InAs quantum dots in GaAs from ion-channeling experiments

Abstract: Strain in and around pyramidal InAs/GaAs quantum dots ͑QD's͒ fabricated by molecular-beam-epitaxy influences the density of states of the confined charge carriers. The presence of strain in QD's is required to explain their optical properties. In this paper MeV ion-channeling experiments are presented which provide evidence for the presence of strain in and around InAs QD's in GaAs. The small dimensions of the QD's ͑typical height 4 nm͒ and the presence of a wetting layer complicate the interpretation of chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…been shown that strain fields due to lattice mismatch S 1.30 -extend from the QDs into surrounding GaAs matrix _ E E over > 10 nm [23]. Such a strain field increases vacancy a 1.25 concentration [23] and is likely to enhance the lateral 0.…”
Section: Sr2mentioning
confidence: 99%
See 1 more Smart Citation
“…been shown that strain fields due to lattice mismatch S 1.30 -extend from the QDs into surrounding GaAs matrix _ E E over > 10 nm [23]. Such a strain field increases vacancy a 1.25 concentration [23] and is likely to enhance the lateral 0.…”
Section: Sr2mentioning
confidence: 99%
“…Such a strain field increases vacancy a 1.25 concentration [23] and is likely to enhance the lateral 0.…”
Section: Sr2mentioning
confidence: 99%
“…It has also been shown that strain field can extend from the QDs into surrounding GaAs matrix over a typical scale of ജ10 nm. [32][33][34] The extended strain field might cause migrations of native defects, such as vacancies and interstitials, to the vicinity of the quantum dots. During our sample growth, because of the relatively thick upper GaAs confining layers, the dots were subjected to an anneal of about 20 min at 580°C, which could enhance the migration of the defects.…”
mentioning
confidence: 99%
“…The strain in and around buried quantum dots is relieved via extended strain fields, which also results in inhomogeneous deformations in the host lattice. It is known from strain measurements and calculations on buried quantum dots that those strain fields extend up to tenths of nm into the host crystal, 13,14 which can be compared to the values for the distortion length we found above.…”
Section: IIImentioning
confidence: 99%
“…After implantation a 10 s rapid thermal anneal ͑RTA͒ in dry nitrogen was applied at a temperature of 1050°C. Two samples were prepared by implanting doses of 3ϫ10 14 and 3ϫ10 15 B/cm 2 .…”
Section: Methodsmentioning
confidence: 99%